Sorption characteristics of fondant candies based on tagatose - Dorozhynska (Onofriichuk), Oksana; Kokhan, Olena; Kambulova, Yuliia (My University, 2021)
This work presents research aimed at establishing the sorption characteristics of sucrose-based fondant candies and fondant candies based on the combination of tagatose with fructose. The sorption curves of both samples of the studied candies were identical in nature and belonged to isotherms of type III, which is characteristic of microporous adsorbents with low energy of adsorbent-adsorbate interaction. The sorption curves were sigmoid, with a well-developed hysteresis, which indicates a completely irreversible process of dehydration. After the desorption process, a small part of the adsorbed moisture remains in the samples on sucrose and tagatose with fructose (0.55 and 0.37%, respectively).The coefficients of determination of both BET and Friendlich models used for the analysis were in the range of 0.85–0.97, which indicates their suitability for describing the isotherms of the studied products. Analysis of the constant characterizing the adsorption energy showed that in the sample based on tagatose and fructose adsorption was 18% higher than in the control sample.The amount of adsorbed moisture in the studied samples of candies at low values of aw had a slight difference, while in the area of capillary moisture (aw = 1.0) this value differed significantly: the amount of adsorbed moisture in the control sample of fondant candies on sucrose was 0.6498 cm3/g, while in the sample based on tagatose and fructose it was 1.5499 cm3/g. The amount of strongly bound moisture in the sample based on tagatose and fructose was greater than in the control sample and was 8.33%, while in the control sample only 5.24%. Therefore, the sorption isotherms allow to predict the behavior of candy samples during their storage at different values of relative humidity. The obtained data can be used for rational selection of packaging material and packaging method to extend the shelf life of developed fondant candies based on tagatose. У даній роботі представлені дослідження з метою встановлення сорбційних характеристик помадних цукерок на основі сахарози та на основі комбінації тагатози з фруктозою. Встановлено, що криві сорбції обох зразків досліджуваних цукерок мають ідентичний характер і відносяться до ІІІ типу ізотерм,що характерно до мікропористих адсорбентів з малою енергією взаємодії адсорбент –адсорбат. Досліджувані криві сорбції сигмоподібні, з досить розвиненим гістерезисом,що свідчить про цілком незворотний процес зневоднення. Після процесу десорбції у зразках на сахарозі і тагатозі з фруктозою залишається незначна частина адсорбованої вологи – 0,55 та 0,37% відповідно. Коефіцієнти детермінації обох моделей БЕТ та Френдліха, що були застосовані для аналізу, знаходяться в межах 0,85–0,97, що свідчить про їх придатність для опису ізотерм досліджуваних виробів. Аналіз константи, що характеризує енергетикуадсорбції, засвідчує, що в зразку на основі тагатози і фруктози адсорбція буде на 18% вища, ніж у контрольному зразку. Кількість адсорбованої вологи у досліджуваних зразках цукерок при низьких значеннях аw має незначну відмінність, тоді як у зоні капілярної вологи (aw=1,0) це значення значно різнилося: кількість адсорбованої вологи в контрольного зразка помадних цукерок на сахарозі становила 0,6498 см3 /г, тоді як у зразку на основі тагатози і фруктози – 1,5499 см3/г. Кількість міцнозв’язаної вологи в зразку на основі тагатози і фруктози є більшою, ніж у контрольному зразку і становить 8,33%, тоді як в контрольному зразку – 5,24%. Одже, дослідження ізотерм сорбції дало змогу спрогнозувати поведінку зразків цукерок під час їх зберігання за різних значень відносної вологості повітря. Отримані дані можна використати для раціонального підбору пакувального матеріалу та способу пакування для подовження термінів зберігання розроблених помадних цукерок на основі тагатози
Keywords: помадна цукерка; тагатоза; фруктоза; сорбція; зберігання; fondant candy; tagatose; fructose; sorption; storage; кафедра технології хлібопекарських і кондитерських виробів